Role of insulin-like growth factor-2 in Alzheimer’s disease induced memory impairment and underlying mechanisms - Chen, Ruiqi; Lu, Xing; Xiao, Anqi; Ma, Junpeng (Frontiers in Cellular Neuroscience, 2025)
Alzheimer’s disease (AD) is the most prevalent type of dementia. Treatments for AD do not reverse the loss of brain function; rather, they decrease the rate of cognitive deterioration. Current treatments are ineffective in part because they do not address neurotrophic mechanisms, which are believed to be critical for functional recovery. Given that structural losses are assumed to be the root cause of cognitive impairment in AD, strengthening neurotrophic pathways may be a useful preventative therapeutic approach. Insulin-like growth factor-2 (IGF2), which is widely expressed in the central nervous system (CNS), has emerged as a crucial mechanism of synaptic plasticity and learning and memory, and many studies have indicated that this neurotrophic peptide is a viable candidate for treating and preventing AD-induced cognitive decline. An increase in IGF2 levels improves memory in healthy animals and alleviates several symptoms associated with neurodegenerative disorders. These effects are primarily caused by the IGF2 receptor, which is widely expressed in neurons and controls protein trafficking, synthesis, and degradation. However, the use of IGF2 as a potential target for the development of novel pharmaceuticals to treat AD-induced memory impairment needs further investigation. We compiled recent studies on the role of IGF2 in AD-associated memory issues and summarized the current knowledge regarding IGF2 expression and function in the brain, specifically in AD-induced memory impairment.